Fe, N-modulated carbon fibers aerogel as freestanding cathode catalyst for rechargeable Zn–Air battery. (February 2022) - Ma, Yu; Chen, Ding; Zhang, Dongdong; Yu, Hao; Zheng, Yapeng; Li, Weijun; Wang, Lin; Liu, Qiao; Yang, Weiyou
Abstract: Freestanding air cathode catalyst with exceptional catalytic bifunctions for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is highly desirable for exploring rechargeable Zn–air batteries (ZABs) with low cost and high reliability. Here, a facile and scalable approach is demonstrated to prepare efficient and robust freestanding cathode catalyst that consists of dispersed Fe3 C nanoparticles, rich Fe-N x /N-C species and carbon fibers networks with large specific surface area, which is based on one-pot in-situ coupling of Fe and N induced active sites within bacterial cellulose-derived carbon fibers networks. Its bifunctional activity parameter (Δ E ) for ORR and OER is 0.79 V, superior to those of single Fe- or N- modulated counterparts, and comparable to the state-of-the-art Pt/C + RuO2 catalyst (0.79 V). This material can be directly used as freestanding and binder-free catalyst layer, and as-assembled ZABs exhibit a larger peak power density (173 mW cm −2 ), higher specific capacity (717 mA h g −1, 10 mA cm −2 ) and better cycle stability (negligible activity decay after 165 h charge/discharge cycles) than those of Pt/C + RuO2 -based devices, representing their potential applications in advanced energy conversion systems. Graphical abstract: We reported the exploration of freestanding cathode catalysts consisted of Fe, N-modulated carbon nanofiber networks and dispersed Fe3 C nanoparticles, which deliver robust mechanical property, excellent catalytic activity and high cycle stability toward oxygen reduction and evolution reactions for rechargeable Zn-air batteries. Image 1 Highlights: Fe and N-induced active sites in bacterial cellulose-derived carbon aerogel was in-situ prepared. The carbon aerogel exhibits high flexibility and robust repetitive compressive duration. The catalyst exhibits excellent catalytic activities to ORR and OER. The carbon aerogel acts as free-standing cathode catalyst for high-performing rechargeable Zn–air battery.